Inpatient temporal trends in open and minimally invasive sacroiliac joint fusions - Parhar, Kanwar; Caruso, Benjamin R.; Alemayehu, Gabriel; Rapport, Richard (International Journal of Research in Orthopaedics, 2025)
Background: Lower back pain is a leading cause of disability worldwide, with sacroiliac joint dysfunction implicated in 15-30% of chronic cases. For this a sacroiliac joint fusion (SIJF) may be performed using either open or minimally invasive surgery (MIS) techniques. Prior to the introduction of unique ICD-PCS codes in 2015, there was limited data on the surgical variables for the different techniques. This study aims to evaluate open and MIS inpatient case trends from 2016-2020. Methods: A retrospective analysis of the national inpatient sample database from 2016 to 2020 was conducted. Patients were identified using ICD-10 PCS codes for open and MIS SIJF procedures. Temporal trends and geographic distribution were analyzed, with demographic and procedural data compared using statistical tests including Mann-Kendall, t-tests, and Chi-square. Results: Among 38,660 inpatient SIJF procedures, 34,590 were open and 3,890 were MIS. The procedures were primarily performed on females, identifying as white, Medicare payers and in urban teaching hospitals (p<0.001). No significant temporal trends in procedural volume were observed for open (p=0.807) or MIS (p=0.462) SIJF from 2016-2020. However, regional analysis revealed majority of the procedures taking place in the Southern region of the United States (p<0.001). Conclusions: Inpatient SIJF volumes remained stable from 2016-2020, with most procedures performed in the South. These findings align with the increasing shift toward outpatient MIS SIJF, as inpatient volumes did not rise despite greater MIS adoption. Future studies should examine outpatient trends to further characterize this shift.